Is the new mission-oriented R&D policy feasible?: evidence from the national R&D programs in Korea using CVM - Yoon, Jiwoong; Lee, Hokyu; Won, Yeonghun (Frontiers in Behavioral Economics, 2024)
The new mission-oriented national R&D programs, aligned with a transformative paradigm to address societal challenges, face challenges in economic feasibility analysis due to the ongoing development of innovative solutions and the time required for marketization.In this study, we employed a Contingent Valuation Method (CVM) to survey 300 Korean households, exploring their willingness to pay for R&D programs hypothetically funded by their taxes. We estimated the mean willingness to pay (WTP) and multiplied it by the total number of households in Korea to project the annual total benefit for each program.Using metrics like the value-added ratio, marketization success rate, and R&D contribution rate, we assessed the economic value of program benefits. Our analysis indicates a total benefit of KRW 285 billion (KRW 242.5 billion net present value) for a total investment of KRW 990 billion (KRW 505.4 billion net present value), with a benefit-to-cost ratio of 2.08, affirming significant economic feasibility.Given the importance of respecting researchers' autonomy, decision-makers may find the CVM a suitable method for validating evidence for new mission-oriented R&D programs across diverse fields.